Optical-fiber thermal-wave-cavity technique to study thermal properties of silver/clay nanofluids - Noroozi, Monir; Radiman, Shahidan; Zakaria, Azmi; Shameli, Kamyar; Deraman, Mohamad; Soltaninejad, Sepideh; Abedini, Alam (European Optical Society, 2014)
Thermal properties enhancement of nanofluids have varied strongly with synthesis technique, particle size and type, concentration and agglomeration with time. This study explores the possibility of changing the thermal wave signal of Ag/clay nanofluids into a thermal diffusivity measurement at well dispersion or aggregation of nanoparticles in the base fluid. Optical-Fiber Thermal-Wave-Cavity (OF-TWC) technique was achieved by using a small amount of nanofluid (only 0.2 mL) between fiber optic tip and the Pyroelectric detector and the cavity-length scan was performed. We established the accuracy and precision of this technique by comparing the thermal diffusivity of distilled water to values reported in the literature. Assuming a linear Pyroelectric signal response, the results show that adding clay reduced the thermal diffusivity of water, while increasing the Ag concentration from 1 to 5 wt.% increased the thermal diffusivity of the Ag nanofluid from 1.524×10−3 to 1.789×10−3 cm2/s. However, in particular, nanoparticles show the tendency to form aggregates over time that correlated with the performance change of thermal properties of nanofluid. Our results confirm the high sensitivity of OF-TWC technique raises the potential to be applied to measuring the optical and thermal properties of nanofluids. Furthermore, this technique allows the extraction of information not obtained using other traditional techniques.